THE COURSE MANAGEMENT MODEL LIFE SKILLS EDUCATION OF THE COURSE AND TRAINING INSTITUTION (LSE-CTI) BASED ON WORLD OF BUSINESS AND INDUSTRY (WBI) GARMENT SEWING PROGRAM IN EX-RESIDENCE OF SEMARANG (Universitas Negeri Semarang, 2014)
Course management had a strategic role in achieving the program of garment sewing courses. The research aimed to develop a course management model LSE-CTI based on WBI that was an effective garment-sewing program. The research approach was Research and Development (R & D). The subject of the research was the managers and the students of the course and training institutionÂ (CTI). The collection of data used was observation technique, interview, questionnaire and documentation. Qualitative descriptive and paired t-test used in analyzing the data. The result of this Research Â showed that the development of course management model life skill education of the course and training institutionÂ (LSE-CTI) based on world of business and industry (WBI) was effective in increasing the competence of managers as well as the students.